Vulnerable Employment among Rural Youth in Karnataka State: A Study of Sustainable Livelihood Capitals - H. Gunashekhar; M. Sreenivasulu; B. Manjunatha; Dayananda Patil; S. Manju Prem; G. N. Damodhara; N. R. Kiran; Priyanka B N; Harishkumar J. (Archives of Current Research International, 2024)
Agriculture in India sustains over half the population, faces a critical challenge as its youth disengage from this sector due to low incomes and high risks, which impedes agricultural reform and competitiveness in the global food market. In 2021, a study was conducted in Karnataka’s Mandya and Ramanagara districts, focusing on assessing the vulnerable employment among 120 randomly selected rural youth in agriculture through constructing a vulnerable employment index. The study revealed that the overall composite vulnerable employment index was 0.63, with human capital being the highest contributor to vulnerable employment (0.80), followed by financial capital (0.78), physical capital (0.68), natural capital (0.63), and social capital (0.57). Notably, 67.50 per cent of surveyed youth face moderate to highly vulnerable employment, primarily due to deficiencies in human capital (72.50%), financial capital (72.50%), natural capital (79.16%), and social capital (77.50%). However, there is a glimmer of hope in the relatively lower vulnerability in physical capital (48.33%). This research highlighted the urgent need to address vulnerable employment among rural youth in agricultural endeavour by investing in relevant skills training and education, providing access to financial resources, ensuring sustainable management of natural capital, and fostering strong social capital through mentorship programs and community engagement.